The encoding of definiteness, specificity and referentiality in Mandarin and Cantonese - Lin, Yi-An (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2008)
This paper is a comparative study of the morphosyntax of the constituents referred to as noun phrases (NP) in traditional grammar. In particular, the focus of this paper centres on two S initie languages, namely Mandarin and Cantonese. The phrase structure of nominais in these languages has been investigated in the literature (i.e., Cheng and Sybesma (1999) on Mandarin and Cantonese, Cheng and Sybesma (2005) on Mandarin, Cantonese, Taiwanese and Wenzhou dialect). In contrast to Cheng and Sybesma’s studies, this paper investigates the internal structure of nominal phrases in terms of Abney’s (1987) Determiner Phrase (DP) Hypothesis, i.e. the hypothesis that nominal phrases are headed by determiners. Furthermore, this paper intends to pursue a unified account of the articulated structure of nominal phrases for cross-linguistic data in line with Perdtsvaig’s (2007) Universal-DP Hypothesis, which asserts that the syntactic structure of the nominal phrase is universal regardless of the presence of lexical items which realize the heads of the functional projections (FPs). More specifically, this paper will propose a Probe-Goal feature valuing model to account for the parametric variation in these two languages within the framework of Chomsky’s (2000, 2001, 2004) phase-based Minimalist Programme (MP).